Fault Detection Variants of the CloudBus Protocol for IoT Distributed Embedded Systems - BARKALOV, A.; TITARENKO, L.; ANDRZEJEWSKI, G.; KRZYWICKI, K.; KOLOPIENCZYK, M. (Advances in Electrical and Computer Engineering, 2017)
Distributed embedded systems have become larger, more complex and complicated. More often, such systems operate accordingly to the IoT or Industry 4.0 concept. However, large number of end modules operating in the system leads to a significant load and consequently, to an overload of the communication interfaces. The CloudBus protocol is one of the methods which is used for data exchange and concurrent process synchronization in the distributed systems. It allows the significant savings in the amount of transmitted data between end modules, especially when compared with the other protocols used in the industry. Nevertheless, basic version of the protocol does not protect against the system failure in the event of failure of one of the nodes. This paper proposes four novel variants of the CloudBus protocol, which allow the fault detection. The comparison and performance analysis was executed for all proposed CloudBus variants. The verification and behavior analysis of the distributed systems were performed on SoC hardware research platform. Furthermore, a simple test application was proposed.